Modulation of cholecystokinin concentrations in the rat hippocampus by chelation of heavy metals. - Stengaard-Pedersen, K (1984)
Previously, we have reported that enkephalins, cholecystokinin, and heavy metals show roughly parallel distributional patterns in the hippocampus. A substantial body of evidence indicates that cholecystokinin-octapeptide (CCK-8) and enkephalins act as neurotransmitters. A CCK-8 degrading enzyme was recently detected in brain synaptosomes. Its activity depended on free thiol groups and the presence of a heavy metal. Since the heavy metal-containing neuropil is closely related to CCK-immunoreactive nerve terminals, we have investigated the effect of metal chelation on CCK components in the rat hippocampus. In vivo treatment of rats with a single dose of the chelating agent diethyldithiocarbamate caused a reversible chelation of heavy metals in the hippocampus. This effect was paralleled by a 3-fold increase in hippocampal content of CCK-8 and a smaller increase in the intermediate forms of CCK (CCK-58, CCK-39, CCK-33). Diethyldithiocarbamate also decreased the spontaneous motility and aggressiveness of the rats. These data show reversible changes of neuronal CCK processing by a drug, and hence they provide additional evidence that CCK is involved in the regulation of neuronal activities.